2016
DOI: 10.1536/ihj.15-476
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of Paroxysmal and Persistent Atrial Fibrillation in Patients With New-Onset Atrial Fibrillation

Abstract: SummaryDiscrimination between paroxysmal and persistent atrial fibrillation (PAF and persistent AF) is important for determining the therapeutic strategy in patients with new-onset AF. We evaluated various clinical factors and P wave morphology to discriminate PAF and persistent AF patients in patients with new-onset AF.The study population consisted of 79 patients with new-onset AF (70.3 ± 10.8 years, female:male 33:46) who were retrospectively selected from 8,632 AF patients in the Kitasato University Hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…1,2) Although the pathophysiological mechanism of AF is not completely understood, the progression of atrial remodeling in AF has been shown to contribute significantly to the perpetuation of AF. [3][4][5] Further, sinus node dysfunction (SND) occurs along with the presence of atrial remodeling in the upper part of the right atrium. 4) Therefore, we hypothesized that patients with AF who have impaired sinus node function would have a lower success rate of catheter ablation of AF and that the sinus node recovery time (SNRT) after defibrillation from a long period of AF could be used to predict recurrences of AF after ablation.…”
mentioning
confidence: 99%
“…1,2) Although the pathophysiological mechanism of AF is not completely understood, the progression of atrial remodeling in AF has been shown to contribute significantly to the perpetuation of AF. [3][4][5] Further, sinus node dysfunction (SND) occurs along with the presence of atrial remodeling in the upper part of the right atrium. 4) Therefore, we hypothesized that patients with AF who have impaired sinus node function would have a lower success rate of catheter ablation of AF and that the sinus node recovery time (SNRT) after defibrillation from a long period of AF could be used to predict recurrences of AF after ablation.…”
mentioning
confidence: 99%
“…To our knowledge, few studies are present in literature about differences between paroxysmal and persistent AF in ECG parameters during SR [10], [13], [14], and none of these focus on beat-to-beat P-wave variability, taking into account also other possible sources of variability in ECG.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of the clinical stage of AF (pathology progression) and the discrimination between paroxysmal and persistent AF is of utmost importance while assessing the therapeutic strategy and subsequent outcomes. Nearly all previous studies have focused on the identification of AF susceptibility or have correlated P-wave morphology to prognosis, but only few studies have analyzed sex-related ECG differences among patients with different clinical types of AF in SR [30]. Differently from these studies, Swiss-AF cohort included patients with known paroxysmal and persistent AF.…”
Section: Ecg Features Of Patients With Different Types Of Afmentioning
confidence: 99%